Short‐Term Safety of Nicotine Replacement in Smokers Hospitalized With Coronary Heart Disease - Quinn R. Pack; Aruna Priya; Tara C. Lagu; Penelope S. Pekow; Auras Atreya; Nancy A. Rigotti; Peter K. Lindenauer (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Little is known about the safety of nicotine replacement therapy (NRT) in smokers hospitalized with coronary heart disease. Methods and Results We examined the short‐term safety of NRT use among smokers hospitalized for coronary heart disease in a geographically and structurally diverse sample of US hospitals in the year 2014. We compared smokers who started NRT in the first 2 days of hospitalization with smokers without any exposure to NRT and adjusted for baseline differences through propensity score matching. Outcomes included inpatient mortality, hospital length of stay, and 1‐month readmission. From 270 hospitals, we included 27 459 smokers (mean age, 58 years; 69% men; 56.9% in intensive care unit), of whom 4885 (17.8%) received NRT (97.2% used the nicotine patch, at a median dose of 21 mg/d for 3 days). After propensity matching, covariates were well balanced within each patient group. Among patients with myocardial infarction, compared with patients who did not receive NRT, those who received NRT showed no difference in mortality (2.1% versus 2.3%; P=0.98), mean length of stay (4.4±3.5 versus 4.3±3.3 days; P=0.60), or 1‐month readmission (15.8% versus 14.6%; P=0.31). Results were similar for patients undergoing percutaneous coronary intervention or coronary artery bypass surgery. Conclusions Among smokers hospitalized for treatment of coronary heart disease, use of NRT was not associated with any differences in short‐term outcomes. Given the known beneficial effects of NRT in treating nicotine withdrawal, reducing cravings, and promoting smoking cessation after discharge, our findings suggest that NRT is a safe and reasonable treatment option.